From Molecules to Interactions to Crystal Engineering: Mechanical Properties of Organic Solids - Saha, Subhankar; Mishra, Manish Kumar; Reddy, C. Malla; Desiraju, Gautam R (Accounts of chemical research, 2018)
Conspectus Mechanical properties of organic molecular crystals have been noted and studied over the years but the complexity of the subject and its relationship with diverse fields such as mechanochemistry, phase transformations, polymorphism, and chemical, mechanical, and materials engineering have slowed understanding. Any such understanding also needs conceptual advancessophisticated instrumentation, computational modeling, and chemical insightlack of such synergy has surely hindered progress in this important field. This Account describes our efforts at focusing down into this interesting subject from the viewpoint of crystal engineering, which is the synthesis and design of functional molecular solids. Mechanical properties of soft molecular crystals imply molecular movement within the solid; the type of property depends on the likelihood of such movement in relation to the applied stress, including the ability of molecules to restore themselves to their original positions when the stress is removed. Therefore, one is interested in properties such as elasticity, plasticity, and brittleness, which are linked to structural anisotropy and the degree to which a structure veers toward isotropic character. However, these matters are still by no means settled and are system dependent. While elasticity and brittleness are probably displayed by all molecular solids, the window of plasticity is perhaps the one that is most amenable to crystal engineering strategies and methods. In all this, one needs to note that mechanical properties have a kinetic component: a crystal that is elastic under slow stress application may become plastic or brittle if the same stress is applied quickly. In this context, nanoindentation studies have shown themselves to be of invaluable importance in understanding structural anisotropy. Several problems in solid state chemistry, including classical ones, such as the melting point alternation in aliphatic straight chain dicarboxylic acids and hardness modulation in solid solutions, have been understood more clearly with this technique. The way may even be open to picoindentation studies and the observation of molecular level movements. As in all types of crystal engineering, an understanding of the intermolecular interactions can lead to property oriented crystal design, and we present examples where complex properties may be deliberately turned on or off in organic crystals: one essentially fine-tunes the degree of isotropy/anisotropy by modulating interactions such as hydrogen bonding, halogen bonding, π···π interactions, and C–H···π interactions. The field is now wide open as is attested by the activities of several research groups working in the area. It is set to take off into the domains of smart materials, soft crystals, and superelasticity and a full understanding of solid state reactivity.